On Copositive Approximation in Spaces of Continuous Functions I: The Alternation Property of Copositive Approximation (Analysis in Theory and Applications, 2017)
In this paper the author writes a simple characterization for the best copositive approximation to elements of $C(Q)$ by elements of finite dimensional strict Chebyshev subspaces of $C(Q)$ in the case when $Q$ is any compact subset of real numbers. At the end of the paper the author applies this result for different classes of $Q$.
Keywords: Strict Chebyshev spaces; best copositive approximation; change of sign.